Disjointed war : military operations in Kosovo, 1999 - Nardulli, Bruce R. (Santa Monica, Calif. : Rand, 2002)
The 1999 military operation in Kosovo had several deficiencies in joint military operations. This study examines all aspects of the conflict, including its political and historical underpinnings, in an attempt to understand these deficiences and to recommend improvements.
At the brink: April 1998 to March 1999 -- Air operation -- Task force hawk -- Enforcing the peace -- Conclusion.
"MR-1406."
Includes bibliographical references (pages 127-147).
Print version record.
eBooks on EBSCOhost
Keywords: North Atlantic Treaty Organization -- Armed Forces -- Yugoslavia; Organisation du traité de l'Atlantique Nord -- Forces armées -- Yougoslavie; North Atlantic Treaty Organization; Kosovo (Republic) -- History -- Civil War, 1998- -- Campaigns; HISTORY -- General; POLITICAL SCIENCE -- Security (National & International); Armed Forces; Military campaigns; Kosovo (Republic); Yugoslavia; Since 1998; History